Development of a Non-Formal Education Program to Enhance the Cooperation in Mathematical Learning Based on Cooperative Learning Concept and Constructivist Theory for Non-Formal Education Students in Bangkok Metropolitan Area - Jintanasoontonsiri, Sarawut (Scholar: Human Sciences, 2014)
This study employed the Cooperative Learning Concept and Constructivist Theory to develop a Non-formal Education Program to Enhance the Cooperation in Mathematics learning. The purposes of the research were to 1) develop a Non-formal Education Program to Enhance the Cooperation in Mathematics learning based on Cooperative Learning Concept and Constructivist Theory for Non-formal Education Students in Bangkok Metropolis; 2) experiment a Non-formal Education Program to Enhance the Cooperation in Mathematics learning based on Cooperative Learning Concept and Constructivist Theory for Non-formal Education Students in Bangkok Metropolis; and 3) study the opinions and factors related to the implementation of the developed a Non-formal Education Program to Enhance the Cooperation in Mathematics learning based on Cooperative Learning Concept and Constructivist Theory for Non-formal Education Students in Bangkok Metropolis. This study was based on the Research and Development in which the samples were twenty-two non-formal education students in the Latphrao District Non-formal and Informal Education Center. The one group pretest-posttest design i.e. single group experiment design was applied in this study. The program implementation lasted thirteen weeks and the total activities lasted one hundred hours.